Procurement and innovation risk management: How a public client managed to realize a radical green innovation in a civil engineering project. Issue 1 (January 2022) - Lenderink, Bart; Halman, Johannes I.M.; Boes, Johan; Voordijk, Hans; Dorée, André G.
Abstract: Public clients' decisions on the procurement and contracting of civil engineering projects have far-reaching effects on the development and implementation of innovations. Two decades ago, a trend towards the use of integrated contracts started to improve constructability and stimulate innovations. However, for radical innovations, the unilateral allocation of innovation risks to the main contractor is undesirable since most of the associated innovation risks are difficult to assess and manage due to the inherent uncertainties. An in-depth case study was used to investigate the development and application of an alternative public-client-led approach to realizing a radical innovation in a civil engineering project. This study shows that: (1) government championship, through a proactive participation of the public client in the initiation, development and implementation of the project and the willingness to bear innovation risks; (2) the application of innovation risk management strategies and the availability of a fall back option; (3) the establishing of favourable organizational and relational conditions, were determinative factors for the successful development and implementation of the intended radical innovation. Furthermore, seven propositions have been derived that together provide instruments through which public clients can actively promote the development and implementation of radical innovations in civil engineering projects. Subject classification codes: Managing Project Risk; Managing Project Innovation; Contract Procurement and Tendering Highlights: The paper describes the successful development and implementation of a radical innovation in a civil engineering project. Radical innovation requires Government championship, Effective innovation risk management and Transdisciplinary cooperation. An entrepreneurial role of the public client is essential to realize a radical innovation in a civil engineering project. Having an existing solution as a fall back option reduces the risk aversion of public client and contract parties. A staged development procedure will create flexibility to cope with technological uncertainties.